2021
DOI: 10.1080/17436753.2021.2014276
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of fibre-reinforced ceramic composites with hierarchical structure

Abstract: This paper reports the 3D printing of fibre-reinforced ceramic composite with hierarchical structures. Through printing precursor formulation, short SiC fibres have been successfully incorporated into silicate materials and gradient porous hierarchical structure has been achieved for the printed parts. The mechanical testing shows a 27% improvement in impact strength, 22% improvement in flexural modulus, and 7.5% in flexural strength compared with parts without fibre reinforcement. High-resolution tomography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Kim et al previously produced a concrete with many large pores by incorporating twisted fibers because the fibers interfere with the distribution of aggregates and contribute to enlargement of the pores [ 55 ]. Another study introduced a ceramic composite with hierarchical structure reinforced by short SiC fibers [ 56 ]. Consistent with these findings, our results confirmed the hierarchically-porous structure created by nanofiber incorporation, which makes it suitable for different needs in bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al previously produced a concrete with many large pores by incorporating twisted fibers because the fibers interfere with the distribution of aggregates and contribute to enlargement of the pores [ 55 ]. Another study introduced a ceramic composite with hierarchical structure reinforced by short SiC fibers [ 56 ]. Consistent with these findings, our results confirmed the hierarchically-porous structure created by nanofiber incorporation, which makes it suitable for different needs in bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…8 Fibrous additives have also been added to reinforce various ceramics to improve their fracture toughness through toughening mechanisms such as CNT pull-out, the bridging effect and crack deflection. 115–117 Maki et al demonstrated that the carbon nanotubes (CNTs) in B 4 C composites can be aligned with their lengths perpendicular to the hot-pressing direction, where the resulting composite pellets have slightly anisotropic thermomechanical properties. 114 In general, with increasing CNT content, the composites with mechanical properties measured perpendicular to the hot-pressing direction have more significant decreases in Young's modulus, Vickers hardness, and coefficient of thermal expansion, and more significant increases in the fracture toughness and thermal conductivities.…”
Section: Practical Considerations Of Plasma-facing Te Devices In Fusi...mentioning
confidence: 99%